Microtubules, in vitro - Correia, John J. (John Joseph); Wilson, Leslie, 1941- (Methods in cell biology ;, 2013)
"There continues to be intense interest in the microtubule cytoskeleton; the assembly, structure and regulation of microtubules; and the numerous motors and accessory proteins that control cell cycle, dynamics, organization and transport. The field continues to grow and explore new aspects of these issues driven immensely by developments in optical imaging and tracking techniques. This 2nd edition brings together current research and protocols in the field of microtubules in vitro and will serve as a valuable tool for cell biologists, biophysicists and pharmacologists who study the microtubule cytoskeleton, as well as for researchers in the biomedical and biotechnology communities with interest in developing drugs that target microtubules, MAPS and motors." -- Publisher's description